Microengineered Materials with Self‐Healing Features for Soft Robotics. (25th March 2021) - Kumar, Vardhman; Ko, Ung Hyun; Zhou, Yilong; Hoque, Jiaul; Arya, Gaurav; Varghese, Shyni
Abstract : Recent advancements in soft robotics have led to the development of compliant robots that can exhibit complex motions driven by living cells, chemical reactions, or electronics. Further innovations are, however, needed to create the next generation of soft robots that can carry out advanced functions and exhibit complex locomotion. Material designs that incorporate "smart" functional properties can contribute to the development of robotic systems with in‐built mechanical responsiveness and functions. Herein, a simple material design that integrates stimuli‐responsive self‐healing and microarchitectural features to control locomotion of soft robots is reported. By employing these material designs along with hyperelastic soft actuators to control propellant dispersion and direction, a circuitry of pneumatic and microfluidic logic is created within a dragonfly‐shaped body that enables the robot to undergo user‐ and environment‐controlled locomotion over water surface. In addition to steering the robot to skim, the material properties are also leveraged to detect water acidification, temperature changes, and hydrophobic impurities such as oil. The design, fabrication, and integration strategies demonstrated herein pave a way for developing futuristic multifunctional soft robots, biomedical devices, and environmental monitoring probe. Abstract : Herein, a multifunctional, entirely soft robot inspired from dragonflies is presented. Smart materials and soft actuators integrated with pneumatic and microfluidic logic circuit are used to control the robot locomotion over water surface while also endowing the robot with environmental sensing, reporting, and adaptation capabilities.